2006
DOI: 10.1007/s10577-006-1050-9
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic aneuploidy in PHA-stimulated lymphocytes of Turner’s syndrome patients

Abstract: In line with the view that aneuploidy destabilizes the karyotype, initiating an autocatalytic process that gives rise to further loss and/or gain of chromosomes, we examined whether a constitutional aneuploidy such as monosomy for one chromosome is associated with sporadic loss and/or gain of other chromosomes. We used PHA-stimulated lymphocytes from eight women with Turner's syndrome (six displayed X chromosome monosomy ranging from 60.2% to 97.9%, and two were below 10%), and eight healthy women who served a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
3
15
0
1
Order By: Relevance
“…Various spindle abnormalities including abnormal shape, length, and chromosome loss from the spindle, presumably leading to chromosome malsegregation to the daughter cells was recently observed in a study using confocal laser scanning microscopy in embryos immunolabeled with antibodies against tubulin (54). These abnormal cell divisions can persist as long as the embryonic genome is not fully active and the cell cycle control is absent (59,60). Low level mosaicism could result in a viable fetus if a core of abnormal cells that form the fetus is overgrown by normal cells (32,40,61).…”
Section: Discussionmentioning
confidence: 92%
“…Various spindle abnormalities including abnormal shape, length, and chromosome loss from the spindle, presumably leading to chromosome malsegregation to the daughter cells was recently observed in a study using confocal laser scanning microscopy in embryos immunolabeled with antibodies against tubulin (54). These abnormal cell divisions can persist as long as the embryonic genome is not fully active and the cell cycle control is absent (59,60). Low level mosaicism could result in a viable fetus if a core of abnormal cells that form the fetus is overgrown by normal cells (32,40,61).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the few previous studies in which the issue has been addressed in nonneoplastic aneuploid cells, typically constitutional trisomy syndromes, have been confusing, even though constitutional aneuploidy ought to provide a cleaner system for studying the connection between chromosomal instability and aneuploidy than cancer cells. These studies also have shown very high frequencies (in excess of 20% when extrapolated to all chromosomes) of somatic aneuploidy in normal (control) blood lymphocytes, comparable with levels in cancerous cells (16,17). We hypothesized that these high estimates were at least partly caused by the high risk of finding cells falsely positive for aneuploidy when assessing minority cell populations in single-probe FISH experiments.…”
Section: Discussionmentioning
confidence: 94%
“…Such cells typically only have a single or a limited set of stem-line chromosome aberrations compared with tumor cell lines, which typically harbor a multitude of genetic lesions, as well as a cancer phenotype. The few earlier studies performed on patients with constitutional aneuploidy have shown high frequencies of additional somatic aneuploidy (somatic mosaicism) in peripheral blood lymphocytes (16,17), which may be interpreted as support for an immediate causal connection between aneuploidy and chromosomal instability. However, these studies are inconsistent, as healthy controls in one study showed a higher frequency of aneusomy than aneuploid cases in the other.…”
mentioning
confidence: 88%
“…Another study from the same group PHA-stimulated lymphocytes from patients with monosomy X (Turner syndrome). The number of aneuploid cells in this monosomy was almost twice the control [21]. Interestingly, these studies observed more frequently monosomies than polysomies.…”
Section: The Effect Of Aneuploidy On Chromosome Instability In Mammalmentioning
confidence: 89%